Merveilleux-scientifique et merveilleux-logique chez Maurice Renard : une épistémologie romancée ? - Hugues Chabot (ReS Futurae)
At the time when Maurice Renard appropriated the designations “merveilleux-scientifique” (scientific-marvellous) and “merveilleux-logique” (logical-marvellous) to formalize the literary genre that he calls for, the development of a logic of scientific discovery is required simultaneously as the program of epistemology. In the French-speaking world, philosophers of science thus question the “logique de l’invention”(logic of invention) (Edouard Le Roy, 1905) or the "logique de l’hypothèse" (logic of the hypothesis) (Ernest Naville, 1895). In the Anglo-Saxon world, some also try specifically to reason the scholar’s creative process by referring it to a "logic of science" (Charles Sanders Peirce, 1878) or to an "experimental logic" (James Mark Baldwin, 1908). In this article, we propose first to review some of the theses developed at that time in the field of philosophy of science concerning the specific creative process at work in scientific thought. In a second time, we will confront these selected pieces of epistemology with the protocols of writing advocated by Maurice Renard to invent stories pertaining to the “merveilleux-scientifique”.